2016
DOI: 10.1007/s00253-016-7329-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell-penetrating peptide and antibiotic combination therapy: a potential alternative to combat drug resistance in methicillin-resistant Staphylococcus aureus

Abstract: The diverse pattern of resistance by methicillin-resistant Staphylococcus aureus (MRSA) is the major obstacle in the treatment of its infections. The key reason of resistance is the poor membrane permeability of drug molecules. Over the last decade, cell-penetrating peptides (CPPs) have emerged as efficient drug delivery vehicles and have been exploited to improve the intracellular delivery of numerous therapeutic molecules in preclinical studies. Therefore, to overcome the drug resistance, we have investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In the era of drug resistance, where pathogen membrane provides a significant barrier, intracellular delivery of antibiotics/drugs by the virtue of CPP, proved to be a vital step in combating drug resistance to some extent (Sparr et al, 2013 ). CPP based conjugates (Ganguly et al, 2008 ; Jain et al, 2015 ) and combination therapy has been explored against several resistant pathogens (Randhawa et al, 2016 ). They have been proved effective against intracellular pathogens too (Gomarasca et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the era of drug resistance, where pathogen membrane provides a significant barrier, intracellular delivery of antibiotics/drugs by the virtue of CPP, proved to be a vital step in combating drug resistance to some extent (Sparr et al, 2013 ). CPP based conjugates (Ganguly et al, 2008 ; Jain et al, 2015 ) and combination therapy has been explored against several resistant pathogens (Randhawa et al, 2016 ). They have been proved effective against intracellular pathogens too (Gomarasca et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that these peptides may be effective if used in combination with antibiotics in the eradication phase of melioidosis treatment at a point when the infected host immune response is strong enough to eliminate the non-replicating bacteria. Recently, Randhawa et al (2016) have elegantly demonstrated the potential of a cell-penetrating peptide in combination with antibiotic therapy to combat bacterial infection. The cell-penetrating ability and low toxicity of NLP-31 and Y43C5A.3 reported in this study proposes a similar combination of antibiotics and AMPs for melioidosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol at concentration 31.25 µg/mL was used along with EtBr to check accumulation. Finally, cells were mounted on poly-L-lysine coated slides with antifade reagent (Invitrogen, Molecular Probes) as described by Randhawa et al (2016). Then coverslip was sealed with the nail-paint and thereafter slide with cell suspension was kept inverted and focused from the bottom and took the pictures at appropriate magnification.…”
Section: Fluorescence Microscopy By Confocal Microscopymentioning
confidence: 99%